(untitled) (Journal of Educational Sciences, 2025)
The article comprehensively examines the actual and significant problem of teaching phraseology of the Russian language to students for whom Kazakh is their native language. In the context of expanding intercultural communications, the possession of stable expressions of the Russian language plays an important role in ensuring effective communication and a deep understanding of cultural nuances. However, linguistic and cultural differences between the Russian and Kazakh languages create certain difficulties in the process of assimilation of phraseological units. In this regard, there is an urgent need to develop innovative and effective pedagogical approaches that take into account the specific needs of this category of students. The proposed study focuses on the potential of using artificial intelligence (AI) as a key tool for creating an adaptive learning environment that can significantly improve the quality of teaching Russian phraseology to Kazakh students. It is proved that traditional teaching methods aimed at the average student do not always take into account individual learning rates, the level of language training and the peculiarities of perception of the material due to the native language and cultural context. In contrast, personalized learning methods based on AI capabilities can provide a more flexible and efficient educational process. The article describes a mechanism for analyzing students’ academic performance at various stages of learning, including identifying typical errors and individual weaknesses in understanding and using Russian phraseological units. Special attention is paid to the ability of AI to generate individualized learning materials, including adapted explanations, usage examples, interactive exercises and control tasks that take into account the level of complexity and identified gaps in the knowledge of each individual student. The following methods were used: analysis of scientific literature, diagnostic test for knowledge of phraseological units (before and after training), adaptive platform for studying phraseological units using AI tools, observation, survey, interview, content analysis of completed tasks, statistical data processing. The theoretical significance of the research is to expand theoretical knowledge about the use of AI in linguodidactics, in particular, in the field of teaching phraseology, to develop a theoretical model of adaptive phraseology teaching using AI, taking into account the specifics of the Kazakh- speaking audience. The practical significance of the research lies in the development of methodological recommendations for Russian language teachers working with Kazakh-speaking students on effective phraseology teaching using adaptive AI technologies. Keywords: adaptive learning, student, phraseology of the Russian language, artificial intelligence, personalization of learning.